Model Inovasi Pengembangan Bahan Ajar Pembelajaran PAI - Sakolan Sakolan (Milenial: Journal for Teachers and Learning, 2021)
This research is motivated by the absence of PAI teaching materials, this study aims to examine the innovation model for the development of PAI learning materials. The type of research used is a literature review, where articles are collected through search engines such as EBSCO, Sciencedirect, Scopus, and Google Scholar published in 2010-2020. The results of the analysis show that the creativity, innovation and competence of teachers in managing the classroom as well as the use of learning media infrastructure in schools, if used properly, greatly influences a good learning atmosphere, so that motivation arises in students in learning. Furthermore, the methods used are all correct and have their advantages and disadvantages, because there is no teaching and learning method that guarantees 100% success. Therefore, in this context, especially teachers, they must be able to optimize their knowledge, abilities and imagination in innovating in the world of education related to the subjects they teach.